Characterization of Fly Ash Alkali Activated Foams Obtained Using Sodium Perborate Monohydrate as a Foaming Agent at Room and Elevated Temperatures - Korat, Lidija; Ducman, Vilma (Frontiers in Materials, 2020)
Alkali activated foams have been extensively studied in recent years, due to their high performance and low environmental footprint compared to foams produced via other methods. Three types of fly ash differing in chemical and mineralogical composition and specific surface were used to synthesize alkali activated foams. Sodium perborate monohydrate was added as a foaming agent and sodium dodecyl sulphate as a stabilizing agent. Foams were characterized at room temperature and after exposure to an elevated temperature (1,000°C). Densities from 1.2 down to 0.3 g/cm3 were obtained, depending on the type of fly ash and quantity of foaming agent added. Correspondingly, compressive strength ranged from 1 to 6 MPa. Comparing all three fly ashes the most favorable results, in terms of density and corresponding compressive strength, were achieved from the fly ash with the highest amounts of SiO2 and Al2O3, as well as the highest amorphous phase content i.e., RI fly ash. Furthermore, after firing to 1,000°C, the density of samples prepared using fly ash RI remained approximately the same, while the compressive strength increased on average by 50%. In the other two types of fly ash the density increased slightly after firing, due to significant shrinkage, and compressive strength increased by as much as 800%. X-ray powder diffraction analysis confirmed the occurrence of a crystallization process after firing to 1,000°C, which resulted in newly formed crystal phases, including nepheline, sodalite, tridymite, and gehlenite.